Trevo 3Mm and/or AXS catalyst 5 for the treatment of medium distal vessel occlusion stroke - results from the ASSIST registry - Ntoulias, Nikos; Brehm, Alex; Miralbés, Salvador; Naravetla, Bharath; Spiotta, Alejandro; Loehr, Christian; Martínez-Galdámez, Mario; McTaggart, Ryan; Defreyne, Luc; Vega, Pedro; Zaidat, Osama O.; Price, Lori Lyn; et al. (Clinical neuroradiology, 2024)
Background: The effect of endovascular therapy (EVT) on the outcome of stroke patients with a medium distal vessel occlusion (MDVO) is unclear. We report the results of MDVO patients treated with the 3mm Trevo stent retriever (SR) and/or the AXS Catalyst 5 distal access catheter. Methods: Data was derived from a prospective, multicenter global registry (ASSIST registry) which enrolled patients treated with operator preferred EVT technique at 71 sites from January 2019 to January 2022. Three techniques were assessed: SR classic, direct aspiration, and a combined approach. Additional inclusion criteria were (a) EVT performed with the 3mm Trevo SR and/or AXS Catalyst 5 distal access catheter on the first pass and (b) an occlusion of the M2 segment or M3 segment of the middle cerebral artery or the A1, A2 or A3 segment of the anterior cerebral artery. The primary outcome was achieving an expanded Thrombolysis in Cerebral Infarction (eTICI) score of 2c or 3 on the first pass, with the primary technique as adjudicated by core lab. The primary clinical outcome measure was a 90-day modified Rankin Scale (mRS) score of 0–2. Results: A total of 155 patients (10.4% of the ASSIST population) were included. Most patients had an M2 occlusion (93.5%). First pass eTICI reperfusion was achieved in 43.1% of the patients. No modifying effect of the frontline technique was found. The rate of mRS 0–2 (overall 65.0%) did not significantly differ between groups. Conclusion: The data suggests that the Trevo 3mm SR and/or the AXS Catalyst 5 may be an option to treat medium distal vessel occlusion, but more data is needed to demonstrate safety and efficacy in this patient cohort. Further improvements are needed regarding materials and techniques to improve reperfusion results in this patient cohort in the future.